Pengaruh Konsentrasi Zat Pengatur Tumbuh Ekstrak Bawang Merah dan Air Kelapa Pada Media MS Terhadap Pertumbuhan Planlet Anggrek Bulan (Phalaenopsis amabilis) - Achmad Ilham; Nova Triani; Ida Retno Moeljani (G-Tech: Jurnal Teknologi Terapan, 2024)
Orchid plant propagation through conventional means is considered less effective and fairly long, so the propagation method used is tissue culture. This study aims to determine the effect of shallot extract concentration and coconut water on the growth of moon orchid (Phalaenopsis amabilis) planlets. The experimental design used was CRD two factors. The first factor is the concentration of shallot extract with 4 levels, namely 0 g/l, 20 g/l, 30 g/l, 40 g/l. The second factor is the addition of coconut water with 4 levels. The second factor is the addition of coconut water with 4 levels, namely 0 ml/l, 50 ml/l, 100 ml/l, 150 ml/l. Data analysis using ANOVA, followed by 5% BNJ test. The parameters used in this study include the addition of planlet height, root length and planlet fresh weight. The results showed that there was an interaction in the combination of 20 g/l shallot extract and 50 ml/l coconut water on all parameters studied.